Bifid mandibular canal: an aberrant anatomic variation - Vijay Kumar (DiscoverSys Inc., 2017)
Objective: To review the literature and to present the report of a case with bifid mandibular canal.Methods: A cone-beam computed tomography scan with incidental finding of bifid mandibular canal was studied and presented in different sections.Results: The MC is a bilateral channel in the mandible that gives the passage to the inferior alveolar nerve, artery, and vein. It usually presents as a single canal where a variation in anatomy has been reported. The bifid mandibular canal is such an anatomic variant where it splits into two canals.Conclusion: The role of CBCT scans can be emphasized while performing procedures on posterior mandibular region, as it can provide the vital information regarding anatomical variation to avoid iatrogenic complication.